1969
DOI: 10.1039/j19690001690
|View full text |Cite
|
Sign up to set email alerts
|

The nature of iridium(IV) iodate

Abstract: The addition of iodate or orthoperiodate ions to red perchlorate solutions of iridium(1v) gives an insoluble blue precipitate of stoicheiometry lr108H,, which can be dehydrated to IrlOGH,. A structure is suggested which involves an iodato-bridge, 103(OH)3, between two iridium atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similarly, when the pH of the solution is increased, the rate of catalyst binding decreases, demonstrating that the catalyst binds faster when retaining aqua ligands rather than more strongly coordinating hydroxo ligands, consistent with a water displacement mechanism. These sites are also rapidly exchanged with the anion present in solution, iodate, which can also act as a ligand 44 . Consistently, we found that an increase in iodate concentration inhibits surface binding; however, a low concentration of iodate is required for heterogenization.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, when the pH of the solution is increased, the rate of catalyst binding decreases, demonstrating that the catalyst binds faster when retaining aqua ligands rather than more strongly coordinating hydroxo ligands, consistent with a water displacement mechanism. These sites are also rapidly exchanged with the anion present in solution, iodate, which can also act as a ligand 44 . Consistently, we found that an increase in iodate concentration inhibits surface binding; however, a low concentration of iodate is required for heterogenization.…”
Section: Resultsmentioning
confidence: 99%
“…Iridium iodate has been shown previously to be catalytically active for water oxidation with sodium periodate. 21 The steric bulk of the butylmalonic acid may prevent aggregation of these nanoclusters, allowing them to reform into discrete trimers after the iodate is consumed.…”
Section: Communicationmentioning
confidence: 99%